Beef cattle prices in the "Pantanal Mato-grossense", Brazil - García, Eduardo Alfonso Cadavid (Pesquisa Agropecuaria Brasileira, 2014)
The price analysis was performed for cyclic and seasonal trend components, identifying the structural forms of price variations for each component. The main conclusions are: (a) by trend analysis, mean animal price increase was estimated being Cr 55.81 (real cruzeiros of 1977) for the lean steer; the price increase of the fat steer was estimated as Cr 5.92/kg of dry weight, 10% higher than for the lean steer. (b) By periodical function analysis, beef cattle cycles were estimated as eight years for the lean steer compared to seven years for the fat steer; (c) The real price variations of the lean steer follow the fat steer prices "pari passu", with a 6.6 month lag phase estimated through the fundamental cycle of periodical functions analysis; (d) The seasonal analysis based on "centered moveable mean" and complemented with the periodical function applied to a "well behaved" cycle showed that the lean steer real price presents rates below 100 between January and August, and increases above 100 from September to November; the temporal difference between harvest of the fat steer and she lean steer was estimated as 1.86 months.